VD_FINDINFO HC / 2016 / 239 vom 9. Februar 2016 - VD Tribunal cantonal (2016)
SÛRETÉS, DROIT D'ÊTRE ENTENDU, REJET DE LA DEMANDE, PROLONGATION DU DÉLAI | 103 CPC (CH), 144 al. 2 CPC (CH), 319 let. b CPC (CH), 99 al. 1 let. d CPC (CH)